FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN MASYARAKAT MEMBAYAR PAJAK KENDARAAN BERMOTOR - Indah Sari AR; Rulan L Manduapessy (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
This study aims to determine the most dominant factors in increasing the level of community compliance in paying two-wheeled vehicle taxes in Mimika Regency. The research method used is descriptive research method and factor analysis tool. The results of this study indicate that of the four independent variables all correlated with the dependent variable. From the variables of awareness, tax law, tax officers and rational attitude, it was found that the most dominant in increasing the level of public compliance in paying two-wheeled vehicle taxes in Mimika Regency was the Tax Law variable.